Rituximab Induces Complete Remission of Proteinuria in a Patient With Minimal Change Disease and No Detectable B Cells - Webendörfer, Maximilian; Reinhard, Linda; Stahl, Rolf A. K.; Wiech, Thorsten; Mittrücker, Hans-Willi; Harendza, Sigrid; Hoxha, Elion (Frontiers in Immunology, 2021)
Minimal change disease (MCD) is a common cause of nephrotic syndrome. Treatment with steroids is usually effective, but frequent relapses are therapeutic challenges. The anti-CD20 antibody rituximab has shown promising results for treatment of steroid-sensitive nephrotic syndrome. Since predictive biomarkers for treatment efficacy and the accurate rituximab dosage for effective induction of remission are unknown, measurement of CD19+ B cells in blood is often used as marker of successful B cell depletion and treatment efficacy. A male patient with relapsing MCD was successfully treated with rituximab, but developed relapse of proteinuria one year later, although no B cells were detectable in his blood. B and T cell populations in the patient’s blood were analyzed before and after treatment with rituximab using FACS analysis. Rituximab binding to B and T cells were measured using Alexa Fluor 647 conjugated rituximab. We identified a population of CD20+ CD19- cells in the patient’s blood, which consisted mostly of CD20+ CD3+ T cells. Despite the absence of B cells in the blood, the patient was again treated with rituximab. He developed complete remission of proteinuria and depletion of CD20+ T cells. In a control patient with relapsing MCD initial treatment with rituximab led to depletion of both CD20+ B and T cells. Rituximab induces remission of proteinuria in patients with MCD even if circulating B cells are absent. CD20+ T cells may play a role in the pathogenesis of MCD and might be a promising treatment target in patients with MCD.